The poliovirus 135S particle is infectious. - Curry, S (1996)
The molecular mechanism of cell entry by unenveloped viruses is poorly understood. The picornaviruses poliovirus, human rhinovirus, and coxsackievirus convert to an altered form (the 135S or A particle) upon interaction with receptors on susceptible cells at 37 degrees C. The 135S particle is thought to be a necessary intermediate because it accumulates inside susceptible cells soon after infection and drugs which inhibit conversion of the virus to this form also prevent infection. However, since a variable fraction of the altered 135S particles is reported to elute unproductively from the surface of susceptible cells, their precise role remains unclear. We have found that poliovirus 135S particles can infect Chinese hamster ovary (CHO) and murine L cells, neither of which are susceptible to infection by native poliovirus. The infectivity of the particles in tissue culture appears to be between 10(3) to 10(5) times less than that of poliovirus on HeLa cells. The 135S particle infectivity was not sensitive to RNase but was greatly reduced by proteolytic treatment. Proteolysis specifically removed the newly exposed N terminus of VP1, a feature which has previously been shown to mediate interactions of the particle with lipid membranes. These results demonstrate that although the infectivity of the 135S particle appears to be receptor independent, it nonetheless requires some property associated with the protein coat. In particular, the N terminus of VP1 plays an important role in the infection process. Our findings are consistent with the hypothesis that the 135S particle is an intermediate in the normal cell entry pathway of poliovirus infection.